Promoter structure and transcriptional activation with chromatin templates assembled in vitro. A single Gal4-VP16 dimer binds to chromatin or to DNA with comparable affinity. - Pazin, M.J.; Hermann, J.W.; Kadonaga, J.T. (Journal of Biological Chemistry, 1998)
To gain a better understanding of the role of chromatin in the regulation of transcription by RNA polymerase II, we examined the relation between promoter structure and the ability of Gal4-VP16 to function with chromatin templates assembled in vitro. First, to investigate whether there are synergistic interactions among multiple bound factors, we studied promoter constructions containing one or five Gal4 sites and found that a single recognition site is sufficient for Gal4-VP16 to bind to chromatin, to induce nucleosome rearrangement, and to activate transcription. Notably, we observed that Gal4-VP16 binds to a single site in chromatin with affinity comparable with that which it binds to naked DNA, even in the absence of ATP-dependent nucleosome remodeling activity. Second, to explore the relation between translational nucleosome positioning and transcriptional activation, we analyzed a series of promoter constructions in which nucleosomes were positioned by Gal4-VP16 at different locations relative to the RNA start site. These experiments revealed that the positioning of a nucleosome over the RNA start site is not an absolute barrier to transcriptional activation. Third, to determine the contribution of core promoter elements to transcriptional activation with chromatin templates, we tested the ability of Gal4-VP16 to activate transcription with TATA box- versus DPE-driven core promoters and found that the TATA box is not required to achieve transcriptional activation by Gal4-VP16 with chromatin templates. These results suggest that a single protomer of a strong activator is able to bind to chromatin, to induce nucleosome remodeling, and to activate transcription in conjunction with a broad range of chromatin structures and core promoter elements.